2021
DOI: 10.48048/tis.2021.45
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of an Extracellular Lipase Produced by Aspergillus oryzae ST11 as a Potential Catalyst for an Organic Synthesis

Abstract: The lipase producing Aspergillus sp. ST11 was identified by molecular and morphological methods. The primers ITS1/ITS4 were used for amplifying the ITS region. It showed that the strain was grouped with Aspergillus oryzae and Aspergillus flavus (98 % bootstrap value). The colony morphology of Aspergillus sp. ST11 on malt extract agar and Czapek yeast agar showed a characteristic of A. oryzae. Therefore, it was identified as Aspergillus oryzae ST11. The lipase produced by the strain was purified and characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Various fungal lipases have been reported to exhibit an ideal temperature from 37˚C to 50˚C, such as Aspergillus sp. ST11 lipase with an optimal activity at 37˚C [61], Galactomyces geotrichum lipase with an optimal activity at 45˚C [62], and Talaromyces thermophilus lipase showing maximum activity at 50˚C [63]. Regarding the influence of temperature on FAL stability, FAL was able to keep most of its catalytic activity at relatively high temperatures (above 40˚C).…”
Section: Plos Onementioning
confidence: 97%
“…Various fungal lipases have been reported to exhibit an ideal temperature from 37˚C to 50˚C, such as Aspergillus sp. ST11 lipase with an optimal activity at 37˚C [61], Galactomyces geotrichum lipase with an optimal activity at 45˚C [62], and Talaromyces thermophilus lipase showing maximum activity at 50˚C [63]. Regarding the influence of temperature on FAL stability, FAL was able to keep most of its catalytic activity at relatively high temperatures (above 40˚C).…”
Section: Plos Onementioning
confidence: 97%
“…However, the enzyme maintained only 30% of its activity for 30 min of incubation period at 70 °C. According to the thermal stability results of a lipase from Aspergillus oryzae ST11 by Paitaid et al [34], the lipase activity was dramatically decreased after 55 °C, while the residual activity was found as 23% at 65 °C. Moreover, Ayinla et al [35] reported that a small purified lipase from Rhizopus oryzae ZAC3 loses 45% and 78% of its activity after incubation for 90 min and 120 min at 65 °C, respectively.…”
Section: Effect Of Temperature On the Activity And Stability Of Purif...mentioning
confidence: 99%